DIGISAFETY: Digitalization of Safety Inventory and Inspection System for Fire Protective Equipment using AppSheet (Study at a Shipbuilding Company) - Mades Darul Khairansyah; Aida Nelawati Rosa (International Conference on Maritime Technology and Its Application, 2024)
The shipbuilding industry is a high-risk sector for accidents, including fires. Indonesian Regulation No. 1 of 1970 mandates worker safety protections, requiring companies to provide and maintain effective fire protection equipment through regular inventory and inspections. Observations show that the fire protection equipment at the shipbuilding company includes fire extinguishers, sprinklers, and hydrant systems. However, the current manual inventory and inspection processes are inefficient, prone to human error, and result in unintegrated data. In the digital era, digital technology is essential for efficient inspections and reporting. This research aims to design an information system for integrating the inventory and inspection of fire protection equipment at the shipbuilding company. The system, developed using AppSheet and integrated with Google Sheets, features Inventory Database, Inspection Dashboard, Inspection Data, Inspection Schedule, Layout Mapping, Maintenance Data, and Standard Operational Procedure (SOP) menus. Additional functionalities include inspection reminder notifications and data download options. The system supports three user roles: Safety Foreman as executor, SHE Supervisor as admin, and SHE Assistant Manager as management. Usability testing with USE questionnaires resulted in a score of 90.3%, categorizing the system as "Highly Feasible" for use. System testing was conducted using usability testing with USE questionnaires, which resulted in a score of 90.3%, categorizing it as "Highly Feasible" for use.